Victor Grant Collection, Album 5, Photograph 245 Elmer Whiteman, John Livingston, Eva W. Livingston, Belle L. McLeroy
Photograph taken at time of 50th wedding anniversary of John and Eva Livingston. Informal full length photograph taken outside. Elmer Whiteman and Belle L. McElroy were the best man and maid of honor at the wedding.
Designation 5.245 in listing stands for Album 5, Photograph 245.
From collection of photographs compiled by Victor Grant, descendant of the Maxwell / Beaubien family.
Located in Office Closet
Keywords: Whiteman, Elemar; Livingston, John; Livingston, Eva W; McElroy, Belle L; Maxwell - Beaubien family; New Mexico -- Whiteman family; New Mexico -- Livingston family; Genealogy - Photographic collection